Social Media Marketing: A Strategic Approach, 2nd Edition - Melissa Barker; Donald I. Barker; Nicholas F. Bormann; Debra Zahay (Cengage Learning, 2016)
Prepare for a successful career in social media marketing or a related field with the unique emphasis found only in SOCIAL MEDIA MARKETING: A STRATEGIC APPROACH, 2E. Each chapter in this popular book includes a section on creating a personal brand, which is useful to current or future professionals at any stage of career development. This edition emphasizes how to use social media techniques, detailed in the book, to develop and maintain a strong personal brand. Helpful discussions also address a full range of online and offline elements you can use to create a viable personal branding strategy. You learn how to use graphical concepts to structure and strategize within what is otherwise a chaotic social media milieu. This edition summarizes many of today's best practices for marketing activities on social media platforms to assist you in functioning most effectively and dealing with the rapid change that is a hallmark of social media.